Treatment and prevention approaches for economically disadvantaged young children: challenges and opportunities. Issue 5 (4th April 2022) - Damashek, Amy; Ross, Denise; Corlis, McKenna; Uwayo, Margaret; Westine, Carl
ABSTRACT: During early childhood, economically disadvantaged children can experience challenges that affect their social-emotional, language, and physical health development across the lifespan. Psychologists have tested several interventions to address developmental problems during early childhood, but information about the degree to which economically disadvantaged children are included in such research is limited. The current paper reviews selected interventions in the areas of social-emotional, language, and physical health challenges to examine the degree to which economically disadvantaged children have been included in early childhood intervention research and to identify efficacious interventions for practitioners and researchers. The review suggests that some areas, such as interventions for Type 1 diabetes and child anxiety disorders, warrant additional research with economically disadvantaged children. The authors recommend increased dissemination, collaboration among early childhood professionals, and the replication of effective interventions with young children and their families to increase their access to quality early childhood care.